Responsibility of E-Commerce Platforms to Consumers for illegal Products in Indonesia - Ariy khaerudin; Olyvia Rosalia; Firayani; Abu Sahman Nasim (Leges Privatae, 2025)
The expansion of e-commerce in Indonesia has significantly transformed digital transactions, offering unparalleled convenience while simultaneously giving rise to pressing legal concerns regarding the distribution of unauthorized goods. Items such as unregulated pharmaceuticals, harmful beauty products, and counterfeit merchandise are increasingly prevalent on online marketplaces, endangering consumer safety. This research adopts a normative juridical framework, incorporating legislative, theoretical, and case-study approaches to examine the extent of liability e-commerce platforms bear in facilitating the trade of illegal products. Under Indonesia’s Consumer Protection Law, Trade Law, and the Electronic Information and Transactions (ITE) Law, these platforms are expected to regulate and oversee transactions, yet in practice, accountability predominantly falls on individual vendors. The principles of strict liability and vicarious liability provide a legal basis for evaluating platform responsibility in such cases. Findings suggest that enforcement mechanisms remain insufficient, allowing gaps in regulatory oversight. To address this, robust policies must be introduced, including stringent verification protocols for sellers and products, alongside stronger governmental supervision of digital commerce. Strengthening these regulatory frameworks will not only enhance consumer rights but also curtail the proliferation of illegal goods across e-commerce platforms, ensuring a safer and more accountable online marketplace.